2011
DOI: 10.1016/j.yexcr.2010.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Delay of migrating leukocytes by the basement membrane deposited by endothelial cells in long-term culture

Abstract: We investigated the migration of human leukocytes through endothelial cells (EC), and particularly their underlying basement membrane (BM). EC were cultured for 20 days on 3 μm-pore filters or collagen gels to form a distinct BM, and then treated with tumour necrosis factor-α, interleukin-1β or interferon-γ. Neutrophil migration through the cytokine-treated EC and BM was delayed for 20-day compared to 4-day cultures. The BM alone obstructed chemotaxis of neutrophils, and if fresh EC were briefly cultured on st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 60 publications
2
25
0
Order By: Relevance
“…These studies showed that activation of MMPs in the tumor increased angiogenesis mainly by increasing bioavailability of VEGF bound to the extracellular matrix at the initial steps of tumor angiogenesis and subsequent signaling for mobilization of BM inflammatory cells including MDSCs 26,49 . However, more recent studies have shown that MDSCs produce MMPs and directly promote angiogenesis and tumor immune suppression 15,504951 . In addition, these studies have shown the pivotal role that VEGF-R1 play in many MDSC functions, including their recruitment by tumors and formation of the pre-metastatic “niche” 21,23 .…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed that activation of MMPs in the tumor increased angiogenesis mainly by increasing bioavailability of VEGF bound to the extracellular matrix at the initial steps of tumor angiogenesis and subsequent signaling for mobilization of BM inflammatory cells including MDSCs 26,49 . However, more recent studies have shown that MDSCs produce MMPs and directly promote angiogenesis and tumor immune suppression 15,504951 . In addition, these studies have shown the pivotal role that VEGF-R1 play in many MDSC functions, including their recruitment by tumors and formation of the pre-metastatic “niche” 21,23 .…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible to construct models, e.g., where ECs are cultured for prolonged periods on porous filters or on collagen gels with stromal cells in close proximity, in which leukocyte recruitment can be followed (e.g., refs. [33,42,53]). Such constructs may be more representative of the in vivo situation, where the proximity of the stroma to the endothelium allows bidirectional cell-cell messages.…”
Section: Experimental Models For Studying the Effects Of Stroma On Lementioning
confidence: 99%
“…Although the focus of this review is on the endothelium and its glycocalyx, it is important to acknowledge that other cellular and noncellular elements such as pericytes and the basement membrane are involved in regulation of transmigration of neutrophils (16). For instance, regions of the basement membrane that are low in laminins appear to be preferentially used by migrating neutrophils (120, 124).…”
Section: Neutrophil Adhesion To Endotheliummentioning
confidence: 99%